1998
DOI: 10.1108/eum0000000006763
|View full text |Cite
|
Sign up to set email alerts
|

New venture support: an analysis of mentoring support for new and early stage entrepreneurs

Abstract: There has been little research on the processes of providing support to new firm entrepreneurs, and little evaluation of the provision of support to existing small firm entrepreneurs through advice, counselling or consultancy. Despite this lack of research, support for new firm entrepreneurs has been largely withdrawn in England and Wales with the focus of support, through Personal Business Advisers (PBAs), targeted at existing small firm entrepreneurs who employ more than 20 people and have the potential for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(73 citation statements)
references
References 0 publications
4
64
0
5
Order By: Relevance
“…Deakins et al (1998) found that mentoring entrepreneurs in new firms had a positive effect, with implications for enhancing firm survival rates. Indeed, the provision of advice can lead to firms surviving because:…”
Section: The Impact Of External Advicementioning
confidence: 99%
“…Deakins et al (1998) found that mentoring entrepreneurs in new firms had a positive effect, with implications for enhancing firm survival rates. Indeed, the provision of advice can lead to firms surviving because:…”
Section: The Impact Of External Advicementioning
confidence: 99%
“…The more knowledge and experience the entrepreneurial mentor has, the more helpful it will be for entrepreneurs in the process of guidance (Deakins et al, 1998).…”
Section: Constructing the Performance Evaluation Index System Of Univmentioning
confidence: 99%
“…It is the timely resolution, or short term sought, from the perspective of a development both sustainable and comprehensive. Therefore, entrepreneurial coaching constitutes a sufficiently personalized approach of coaching, allowing executive beginners to develop their leadership skills (Bisk, 2002;Deakins et al, 1998;Graham and O'Neill, 1997).…”
Section: Entrepreneurial Coachingmentioning
confidence: 99%